دراسة واقع أبعاد جودة الخدمات المقدمة للعملاء في شركات النقل البحري المتعاملة مع مرفأ اللاذقية - نصور, ريزان; قميرة, خليل (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف البحث إلى دراسة واقع أبعاد جودة الخدمات (الاعتمادية, الاستجابة, الضمان, الملموسية, التعاطف) المقدمة للعملاء في شركات النقل البحري المتعاملة مع مرفأ اللاذقية. اعتمد البحث على المنهج الوصفي, وأسلوب المسح الاجتماعي. أما عينة الدراسة فهي عينة ميسرة من عملاء شركات النقل البحري خلال فترة تطبيق البحث, حيث تمّ استقصاء آراء (269) عميل, وأعيد (244) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (90.71%).* تحظى الشركات محل الدراسة بثقة واستحسان العملاء, حيث تحرص على تقديم الخدمات في الأوقات المحددة, وهذا ما يؤكده بعد الاعتمادية, حيث جاء بالمرتبة الرابعة بين أبعاد جودة الخدمة. * ترغب الشركات محل الدراسة في مساعدة العملاء, حيث تنظم فرق عمل لضمان تقديم خدماتها طوال الوقت, كما تبسط إجراءات العمل قدر الإمكان لضمان السرعة والسهولة في تقديم الخدمة, وهذا ما يؤكده بعد الاستجابة, حيث جاء بالمرتبة الخامسة بين أبعاد جودة الخدمة. * تحافظ الشركات محل الدراسة على سرية المعلومات الخاصة بالعملاء, حيث تمتاز بسمعة ومكانة جيدة لدى أفراد المجتمع, ويشعر العملاء بالأمان عند التعامل مع هذه الشركات, وهذا ما يؤكده بعد الضمان, حيث جاء بالمرتبة الثالثة بين أبعاد جودة الخدمة.* تمتلك الشركات محل الدراسة تجهيزات وأجهزة ومعدات تقنية حديثة, كما تتوفر في الشركة مرافق مادية وتسهيلات ملائمة جذابة, وهذا ما يؤكده بعد الملموسية, حيث جاء بالمرتبة الأولى بين أبعاد جودة الخدمة. * يعطي العاملون في الشركات محل الدراسة الوقت الكافي لخدمة العملاء, حيث تضع الشركات مصالح العميل في مقدمة اهتمامات الإدارة والعاملين, كما يمتلك العاملون في الشركة المعرفة والدراية باحتياجات ورغبات العملاء, وهذا ما يؤكده بعد التعاطف, حيث جاء بالمرتبة الثانية بين أبعاد جودة الخدمة. The research aims to study the reality of the quality of service dimensions (reliability, responsiveness, security, tangibility, empathy) to customers in the marine transportation companies dealing with the port of Latakia. Find adopted a descriptive approach, style social survey. The sample of the study are soft sample of shipping companies clients during the period of application of research, where the views of the survey (269) client, and re (244) questionnaire complete and valid for statistical analysis, and response rate (90.71%).*The companies are under study with confidence and desirability of customers, is keen on providing services in the specified times, and this is confirmed after the reliability, where he was ranked fourth among the service quality dimensions.*The companies want to replace the study in helping customers, where organize work teams to ensure delivery of its services all the time, and simplify working procedures as much as possible to ensure the speed and ease of service, and this is confirmed after the response, where he was fifth rank among the service quality dimensions.*The companies keep under consideration the confidentiality of customer information, where the advantage of a good reputation and prestige of the members of the community, and customers feel safe when dealing with these companies, and this is confirmed after the warranty, where he was ranked third among the service quality dimensions.*The companies under study have facilities and equipment of modern technology, are also available at the company's physical facilities and adequate facilities attractive, and this is confirmed after the tangibility, where he was the first prize among the service quality dimensions.*gives workers in companies under study, the time to customer service, which puts corporate interests of the client at the forefront of the concerns of management and staff, as has the workers in the company's knowledge and know-how to the needs and desires of customers, and this is confirmed after sympathy, where he was ranked second among the service quality dimensions.